Manajemen Tatalaksana Neuritis Optik Demielinasi - Okta Della Susmitha; Muhammad Yusran (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2020)
Introductions: Optic Neuritis (ON) is defined as inflammation of the optic nerve, which is mostly idiopathic. But it can be linked to other causes such as demyelinating lesions, autoimmune disorders, infections and inflammation. Of all these, multiple sclerosis (MS) is the most common cause of demyelinating ON. Objectives: To determine the diagnosis and management of demyelinating optic neuritis. Methods: This article was produced using the literature review method, involving 29 references, both books and national or international journals. Results: ON occurs due to an inflammatory process that leads to T-cell activation that can cross the blood brain barrier and cause hypersensitivity reactions to nerve structures. The exact mechanism is unknown. The clinical diagnosis of ON consists of three classic symptoms namely vision loss, periocular pain and dyschromatopsia. This requires careful ophthalmic, neurological and systemic examination to distinguish between specific and non-specific ON. A differential diagnosis is needed to make an appropriate management plan. Discussions: According to the Optic Neuritis Treatment Trial (ONTT), the first treatment is intravenous methylprednisolone with faster recovery and fewer possible cases of relapse and conversion to MS. However, oral prednisolone alone is contraindicated because of an increased risk of relapse. Controlled High-Risk Subjects Avonex® Multiple Sclerosis Prevention Study (CHAMPS) and Early Treatment of MS Study (ETOMS) and have reported that treatment with interferon ?-1a, with the result of reducing the risk of MS characteristic characteristics from MRI. Contrast sensitivity, color vision and visual fields are parameters that remain largely disturbed even after recovery of good visual acuity. Conclusions: Management of dominant demyelinating optic neuritis is given steroids and ?-1a interferon. Keywords: demyelination, multiple sclerosis, optic neuritis, management